Karakteristik Pembiayaan dan Non Performing Finance Perbankan Syariah 2015–2018 - Putra, Rosyid Nur Anggara (MALIA: Journal of Islamic Banking and Finance, 2019)
Each type of contract in financing in a Sharia Bank has differentcharacteristics. This can not be separated from the type of transaction used infinancing. This study aims to analyze the effect of financing characteristicsbased on the contract in the distribution of funds, namely: mudharabahfinancing, musyarakah financing, murabahah financing and qardh loans tofinancing risk which is proxied by the ratio of non-performing finance (NPF).The research is a quantitative associative study with the object of a shariacommercial bank in Indonesia. The sampling technique used a purposivesampling technique where the number of samples analyzed was 66 consistingof 11 Islamic Commercial Banks with the period 2011-2016. The analysisshows that mudharabah financing has a positive effect on NPF, murabahahfinancing has a negative effect on NPF. While musyarakah and qardhul hasanfinancing does not affect the NPF ratio.